Land conversion for suburban housing : a study of urbanization around Warsaw and Olsztyn, Poland - Adam Wasilewski; Krzysztof Krukowski (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2002)
In the 1990's, urban demand for housing land around city-agglomerations increased rapidly. Additionally, the decreasing profitability of agricultural production caused farmers, who are able to freely decide on land turnover, to be interested in land sale for non-agricultural purposes. At the same time, Polish counties received the status of selfgovernments, which then imposed their will upon local economic development. In this way, counties became responsible for land management as well, and started supporting the process of land conversion, perceived as a factor of the above development. Such implications have created the following situation: decentralisation and the extension of private control over land has led to the loss of rural landscapes in Poland, because farmers, county self-governments and rural society in general gain from the conversion of agricultural to housing land. Therefore, field research has been exercised at the county level. For the investigation, two counties, located in regions differentiated by economic growth, were selected. The data were collected through the collection of archival records, documentation review and semi-structured interviews.
Keywords: 330; Suburbanisierung; Bauland; Landwirtschaftliche Bodennutzung; Urbanisierung; Warschau <Woiwodschaft>; Olsztyn <Woiwodschaft>